Phytochemical Screening and Anti-Inflammatory Studies of Tapinanthus globiferus (A. Rich) Teigh. Leaves Three Extracts - Celestine Jeremiah; Umar Adam Katsayal; Aliyu Nuhu; Sherifat Bola Anafi; Mustapha Adeojoh Ibrahim; Hadiza Dijie Nuhu (Tabriz University of Medical Sciences, 2019)
Background: Tapinanthus globiferus (A. Rich) Teigh. (Loranthaceae) is an excellent medicinal plant in terms of efficacy and also traditionally used for the treatment of various diseases including inflammations, cancer, diabetes and strokes. This study was designed to assess the anti-inflammatory activity of the leaf extracts of T. globiferus in wistar rats and identify phytochemical constituents of the extracts responsible for the observed activity. Methods: Tapinanthus globiferus leaves was extracted with hexane, ethyl acetate and methanol in a soxhlet apparatus. The extracts were subjected to qualitative phytochemical analysis, toxicity and anti-inflammatory activity using carrageenan-induced paw oedema in wistar rats. Piroxicam (20 mg/kg) was used as reference standard. The data were analyzed by one-way analysis of variance with significant level set at p≤0.05. Results: The percentage yield from the gradient extraction of T. globiferus leaves showed methanol to be the highest and the chromatographic analysis visualized with specific reagents confirmed the presence of steroids/triterpenes, phenolic compounds and flavonoids in the leaf of T. globiferus. LD50 was above 2,000 mg/kg and no death was recorded. The hexane, ethyl acetate and methanol leaf extracts of T. globiferus at 250, 500 and 1,000 mg/kg produced a significant decrease in paw oedema (p≤0.05) with percentage inhibition at the first and third hour for hexane, ethyl acetate and methanol extract respectively. The methanol extracts recorded the highest inflammatory inhibition percentage. Conclusion: These finding revealed that the leaf of T. globiferus has anti-inflammatory activity and this justified its traditional use in the treatment of inflammation.